Construction of a Fish‐like Robot Based on High Performance Graphene/PVDF Bimorph Actuation Materials. Issue 6 (31st March 2016) - Xiao, Peishuang; Yi, Ningbo; Zhang, Tengfei; Huang, Yi; Chang, Huicong; Yang, Yang; Zhou, Ying; Chen, Yongsheng
Abstract : Smart actuators have many potential applications in various areas, so the development of novel actuation materials, with facile fabricating methods and excellent performances, are still urgent needs. In this work, a novel electromechanical bimorph actuator constituted by a graphene layer and a PVDF layer, is fabricated through a simple yet versatile solution approach. The bimorph actuator can deflect toward the graphene side under electrical stimulus, due to the differences in coefficient of thermal expansion between the two layers and the converse piezoelectric effect and electrostrictive property of the PVDF layer. Under low voltage stimulus, the actuator (length: 20 mm, width: 3 mm) can generate large actuation motion with a maximum deflection of about 14.0 mm within 0.262 s and produce high actuation stress (more than 312.7 MPa/g). The bimorph actuator also can display reversible swing behavior with long cycle life under high frequencies. on this basis, a fish‐like robot that can swim at the speed of 5.02 mm/s is designed and demonstrated. The designed graphene‐PVDF bimorph actuator exhibits the overall novel performance compared with many other electromechanical avtuators, and may contribute to the practical actuation applications of graphene‐based materials at a macro scale. Abstract : A graphene‐poly‐(vinylidene fluoride) (PVDF) bimorph actuator is fabricated. The actuator can fast generate large actuation motion and produce high actuation stress due to the differences in coefficient of thermal expansion between the two layers and the converse piezoelectric effect and electrostrictive property of PVDF. On this basis, a fish‐like robot that can swim at the speed of 5.02 mm s −1 is designed and demonstrated.